Evaluation of the economic effect of biological therapy in patients with severe COVID-19 and cytokine storm - M. Yu. Frolov; A. S. Salasyuk; V. A. Rogov (Фармакоэкономика)
Aim. The study aimed to assess the economic effect of biological therapy with anti-interleukin (IL)-6 drugs: tocilizumab, olokizumab, and levilimab in patients with severe COVID-19 and cytokine storm.Materials and Methods. An assessment of the economic consequences of severe COVID-19 therapy was carried out using the cost of illness analysis in a model developed in Microsoft Excel 2016 (Microsoft, USA). The direct medical costs of providing care for COVID-19 were taken into account (ICU service, the cost of biological therapy, and the use of glucocorticosteroids (GC)). Data from a prospective, historical controlled CHIC study conducted in the Netherlands were used as a source of efficacy. A mathematical model has been developed for extrapolating the CHIC study results to clinical outcomes (transfer to mechanical ventilation, discharge from ICU, lethal outcome) and forecasting the costs of managing severe patients with COVID-19 in real clinical practice in the Russian Federation.Results. The reduction in the cost of therapy when the hypothesis of equal efficacy of tocilizumab, olokizumab, and levilimab is accepted by reducing the cost of drug therapy will be 1,251,698.99 rubles per 72 patients when comparing olokizumab with tocilizumab and 939,718.84 rubles per 72 patients when comparing olokizumab with levilimab.Conclusion. Anti-interleukin (IL)-6 drugs in combination with GC are an effective treatment option for moderate to severe patients with COVID-19 and cytokine storm symptoms. This group of drugs is indicated as the main one for the treatment of this condition.